The Influence of the Project Based Learning Model to Improve Students' Creative Thinking Skills in IPAS Subjects in Class IV of UPTD SD Negeri 124401 Pematangsiantar - Jihan Nurhadillah Saragih; Emelda Thesalonika; Asister Fernando Siagian (Journal of Pedagogi, 2025)
This study aims to determine the effect of the Project Based Learning model on improving students' creative thinking skills in the Natural Sciences subject with the material "My Indonesia is Rich in Culture" in class IV of UPTD SD Negeri 124401 Pematangsiantar. The research used an experimental method with a One Group Pretest-Posttest Design. The research sample consisted of 25 fourth-grade students. The research instrument was an essay test that had been validated by two validators with high content, construct, and language validity results (Aiken 0.80 V 1.00). The results showed that the average pretest score was 48.08 and the posttest score was 88.00, with an N-Gain value of 0.7832, which is considered high. Thus, the Project Based Learning model is effective in improving students' creative thinking skills in science learning.